IDENTIFYING FINANCIAL MANAGEMENT BEHAVIOR IN MILLENIAL GENERATION - Novia Junita; Robin Robin; Yulfiswandi Yulfiswandi (Universitas Pakuan, 2021)
ABSTRACTThis study aims to examine the effect of financial knowledge, financial attitudes, financial socialization, locus of control on financial management behavior. The research sample is the millennial generation in Batam City which was selected by purposive sampling method who were born in 1984–1999. Research data were collected by questionnaire. The data were analyzed using normality, validity, heteroscedasticity, and t and F tests. The results of this study concluded that financial knowledge, financial attitudes, primary agents of financial socialization, secondary agents of financial socialization, childhood consumer experiences had a significant positive effect on financial management behavior, while other variables are not significant. The managerial implications are doing financial planning, building a saving pattern, having a sense of responsibility, and setting financial goals. Parents are expected to provide financial concepts since childhood, build the habit of saving since childhood by giving pocket money and teach how to allocate money. ABSTRAKPenelitian ini bertujuan untuk meneliti pengaruh pengetahuan keuangan, sikap keuangan, sosialisasi keuangan, locus of control terhadap perilaku pengelolaan keuangan. Sampel penelitian adalah generasi milenial di Kota Batam yang dipilih dengan metode purposive sampling yang lahir pada tahun 1984–1999. Data penelitian dikumpulkan dengan kuesioner. Data dianalisis menggunakan uji normalitas, validitas, heteroskedesitas, dan uji t dan F. Hasil penelitian ini menyimpulkan bahwa pengetahuan keuangan, sikap keuangan, agen primer sosialisasi keuangan, agen sekunder sosialisasi keuangan, pengalaman konsumen masa kecil berpengaruh signifikan positif terhadap perilaku pengelolaan keuangan, sedangkan variabel lainnya tidak signfikan. Implikasi manajerial adalah melakukan perencanaan keuangan, membangun pola menabung, memiliki rasa tanggung jawab, dan menetapkan tujuan keuangan. Orang tua diharapkan memberikan konsep keuangan sejak kecil, membangun kebiasaan menabung sejak kecil dengan memberikan uang saku dan mengajarkan cara mengalokasikan uang.